Rewiring of the Serotonin System in Major Depression - Vahid-Ansari, Faranak; Albert, Paul R. (Frontiers in Psychiatry, 2021)
Serotonin is a key neurotransmitter that is implicated in a wide variety of behavioral and cognitive phenotypes. Originating in the raphe nuclei, 5-HT neurons project widely to innervate many brain regions implicated in the functions. During the development of the brain, as serotonin axons project and innervate brain regions, there is evidence that 5-HT plays key roles in wiring the developing brain, both by modulating 5-HT innervation and by influencing synaptic organization within corticolimbic structures. These actions are mediated by 14 different 5-HT receptors, with region- and cell-specific patterns of expression. More recently, the role of the 5-HT system in synaptic re-organization during adulthood has been suggested. The 5-HT neurons have the unusual capacity to regrow and reinnervate brain regions following insults such as brain injury, chronic stress, or altered development that result in disconnection of the 5-HT system and often cause depression, anxiety, and cognitive impairment. Chronic treatment with antidepressants that amplify 5-HT action, such as selective serotonin reuptake inhibitors (SSRIs), appear to accelerate the rewiring of the 5-HT system by mechanisms that may be critical to the behavioral and cognitive improvements induced in these models. In this review, we survey the possible 5-HT receptor mechanisms that could mediate 5-HT rewiring and assess the evidence that 5-HT-mediated brain rewiring is impacting recovery from mental illness. By amplifying 5-HT-induced rewiring processes using SSRIs and selective 5-HT agonists, more rapid and effective treatments for injury-induced mental illness or cognitive impairment may be achieved.